Novel chip-based isoelectric focusing device for fractionation of bacteria prior to their mass spectrometry identification - Duša, Filip; Šalplachta, Jiří; Horká, Marie; Lunerová, Kamila; Rosenbergová, Kateřina; Kubíček, Oldřich (Analytica chimica acta, 2022)
We have developed a planar chip utilizing divergent geometry of separation channel capable of vertical free-flow electrophoresis of particles at flows of lower hundreds of microliters per minute. The divergent flow isoelectric focusing (DF-IEF) chip consists of two sheets of clear polystyrene glass which serve as a base with working channels and a top cover sealing the separation channel. Optimization showed that the chip is capable to form pH gradient within 1 h and separation is completed in 5 or more minutes depending on the sample volume. The vertical position of the chip enabled analysis of sedimenting particles including microorganisms. Four different common bacteria species inactivated with H2O2 vapors were analyzed in a series of experiments. Isoelectric points were determined with capillary isoelectric focusing with following fractionation using DF-IEF with intact cell matrix-assisted laser desorption/ionization mass spectrometry detection. The DF-IEF chip fractionation proved promising for bacterial sample preparation from complex matrices for subsequent identification of whole cells by mass spectrometry.
Keywords: Chemical Fractionation; Isoelectric Focusing; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Isoelectric focusing; peroxid vodíku; Intact cell; isoelektrická fokusace; Hydrogen Peroxide; Mass spectrometry; Bacteria; chemická frakcionace; Chip